Dynamic Stability Control of Sudan National Grid Using Power System Stabilizer (University of Khartoum Engineering Journal, 2022)
Application of power system stabilizers (PSS), as supplementary control signals for the excitation system in order to damp the low frequency, generator angle, speed variation, generator power, voltage magnitude and power flow oscillations. This paper presents the application of robust decentralized power system stabilizer (PSS) design approaches, for Sudan power system which consists of 41 machines with 167 buses. The paper mainly focus on operator testing of robust decentralized control techniques for power systems, and the optimal control approach to robust control design. Results of robust decentralized control design approaches are defined by using state space model equations. Also for testing dynamic stability Lyapunov theorem is used. The simulations were carried out using symmetrical fault and results presented by Power System Analysis Toolbox, MATLAB.